Malnutrition Status and Associated Factors in Cardiac Patients Admitted to Heart Hospital, in the North of Iran. Issue 2 (3rd April 2019) - Mahdavi-Roshan, Marjan; Salari, Arsalan; Hasandokht, Tolou; Rahbar-Taramsari, Morteza
Abstract: The objective of study was to evaluate the prevalence of malnutrition and associated factors in cardiac patients in the north of Iran. This cross-sectional study was done on 430 cardiac patients, who were admitted to the only heart hospital in the north of Iran. The malnutrition status was assessed based on "Malnutrition Universal Screening Tool" (MUST). The data was analyzed using SPSS software. The mean age of patients was 63.5 ± 12.67 years. The commonest cause of hospitalization was acute coronary syndrome. 31.4% patients had history of admission in the past 12 months. The prevalence of malnutrition was 14%, 7.7%, and 6.3% had medium and high risk of malnutrition, respectively. Patients with history of one time admission were 2.7 times more likely to be malnourished. The odds ratio for more than one time of hospital admission was 3.54. Malnutrition is likely to be present when the cardiac patients are admitted to hospital in Gilan province, in northern Iran.